Distribuição de renda no Brasil: enfoque na renda do trabalho (2001-2015) - Ribeiro, Márcio Luiz (2019)
This study analyzed the inequality of the distribution of the household income per capita (RDPC) from work in Brazil between 2001 and 2015 based on data from the National Household Sample Survey (PNAD). For such, inequality indexes were estimated, the participation of the work share in the formation of the RDPC and the degree of progressivity of these shares was verified, and the variation in the Gini index was decomposed by the composition effect and concentration effect. The results showed that the RDPC inequality fell, on average, 1.12% per year by the Gini index in Brazil between 2001 and 2015, a decrease of 13.60% in relation to the year 2001. The shares of labor income were responsible for about 3/4 of the total RDPC formation in the period analyzed, indicating that much of the income inequality can be revealed and/or generated in the labor market. The degree of progressivity indicated that only the share of the income of the employees and self-employed contributed to decreasing the income inequality, however, these shares were little progressive. About 3/4 of the Gini index formation was given by the labor income in the analyzed period. Finally, the decomposition of the Gini index by composition effect and concentration effect, for the period 2001-15, showed that the shares of labor income accounted for 57.64% of the fall in income inequality, and the composition effect was 48.40% and the concentration effect was 9.24%. Thus, shares of labor income have a major influence on income inequality if they become more progressive over time. Nonetheless, even though they are not very progressive, these shares have effectively contributed to the fall in income inequality, which could potentially be much higher, given their high participation in the RDPC.